Why Have Traffic Fatalities Declined in Industrialized Countries? Implications for Pedestrians and Vehicle Occupants - Kopits, Elizabeth (World Bank, Washington, DC, 2012)
This paper examines whether the relationship between traffic fatalities and per capita income is the same for different classes of road users and investigates the factors underlying the decline in fatalities per vehicle kilometer traveled (VKT) observed in high-income countries over recent decades. Formal models of traffic fatalities are developed for vehicle occupants and pedestrians. Reduced-form approximations to these models are estimated using panel data for 32 high-income countries over 1964-2002. The results suggest that the downward-sloping portion of the curve relating traffic fatalities per capita to per capita income is due primarily to improved pedestrian safety. The more detailed models shed light on some factors influencing pedestrian fatalities per VKT, but much of the reduction in pedestrian fatalities remains unexplained. Increased motorization and a reduction in the proportion of young drivers in the population, however, clearly played a role. In contrast to pedestrian fatalities, occupant fatalities do not show a significant decline with income. What does explain declines in occupant fatalities per VKT are reductions in alcohol abuse and improved medical services, and a reduction in young drivers. The importance of demographic factors suggests that in countries where young persons (between 15 and 24 years of age) comprise an increasing share of the driving population, adopting policies to improve young driver education and reduce speeds will be crucial.